Capecitabine-based chemotherapy in early-stage triple-negative breast cancer: a meta-analysis - Bai, Jie; Yao, Xufeng; Pu, Yinghong; Wang, Xiaoyi; Luo, Xinrong (Frontiers in Oncology, 2023)
The efficacy and safety of adjuvant capecitabine in early-stage triple-negative breast cancer remains undefined. A meta-analysis was conducted to elucidate whether capecitabine-based regimens could improve survival in early-stage triple-negative breast cancer (TNBC).The current study searched Medline, Embase, Cochrane Library, Web of Science and ClinicalTrials.gov proceedings up to 2023.9. Disease-free survival (DFS), overall survival (OS) and grade 3-4 adverse events (AEs) were assessed. Extracted or calculated hazard ratios (HRs) and odds ratios (ORs) with 95% confidence intervals (CIs) were pooled.The capecitabine-based regimens showed significant advantages in DFS (HR = 0.81, 95% CI: 0.73-0.90; P <.001) and OS (HR = 0.75, 95% CI: 0.65-0.87; P <.001) from twelve randomized controlled trials (RCTs) with 5390 unselected participants. Subgroup analysis of DFS showed analogous results derived from patients with lymph node negative (HR = 0.68, 95% CI: 0.50-0.92; P = .006) and capecitabine duration no less than six cycles (HR = 0.73; 95% CI: 0.62-0.86; P < .001).Improvement of DFS in the addition group (HR = 0.77, 95% CI: 0.68-0.87; P <.001) and adjuvant setting (HR = 0.79, 95% CI: 0.70-0.89; P <.001) was observed. As to safety profile, capecitabine was associated with more frequent stomatitis (OR = 5.05, 95% CI: 1.45-17.65, P = .011), diarrhea (OR = 6.11, 95% CI: 2.12-17.56; P =.001) and hand-foot syndrome (OR = 31.82, 95% CI: 3.23-313.65, P = .003).Adjuvant capecitabine-based chemotherapy provided superior DFS and OS to early-stage TNBC. The benefits to DFS in selected patients with lymph node negative, the addition and extended duration of capecitabine were demonstrated.